2012
DOI: 10.1007/s00586-011-2135-5
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year survey reveals differences in GP management of neck and back pain

Abstract: Purpose Clinical guidelines provide similar recommendations for the management of new neck pain and low back pain (LBP) but it is unclear if general practitioner's (GP) care is similar. While GP's management of LBP is well documented, little is known about GP's management of neck pain. We aimed to describe GP's management of new neck pain and compare this to GP's management of new LBP in Australia between April 2000 and March 2010. Methods All GP-patient encounters for a new (i.e. first visit to any medical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Our study found less than half of new consulters for musculoskeletal pain received an analgesic. A previous study of those aged over 50 consulting in primary care for musculoskeletal pain, and who had not consulted in the previous 30 days, also reported that less than half were prescribed analgesics [ 17 ] and this is also similar to findings from studies focussed on neck and back pain [ 6 , 7 ] and on osteoarthritis [ 18 ]. It is feasible that GPs may be following guidelines that recommend the early use of exercise and other physical therapies with or without analgesia and further research is needed to determine if this is happening [ 1 , 19 ].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Our study found less than half of new consulters for musculoskeletal pain received an analgesic. A previous study of those aged over 50 consulting in primary care for musculoskeletal pain, and who had not consulted in the previous 30 days, also reported that less than half were prescribed analgesics [ 17 ] and this is also similar to findings from studies focussed on neck and back pain [ 6 , 7 ] and on osteoarthritis [ 18 ]. It is feasible that GPs may be following guidelines that recommend the early use of exercise and other physical therapies with or without analgesia and further research is needed to determine if this is happening [ 1 , 19 ].…”
Section: Discussionsupporting
confidence: 61%
“…Despite guidance advocating similar approaches for neck and low back pain, their management strategies have been shown to be different in terms of the analgesics prescribed and other therapies [ 6 ]. Whilst even with the introduction of guidelines, analgesic prescribing in patients with low back pain has not been shown to change [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spinal pain (neck or low back pain) is the leading cause of disability worldwide,1 2 and commonly managed in general practice by prescription of medicines 3 4. Clinical guidelines recommend non-steroidal anti-inflammatory drugs (NSAIDs) as a second-line analgesic after paracetamol, with third choice being opioids 5.…”
Section: Introductionmentioning
confidence: 99%
“…The authors support the value of these well-established and expert-derived guidelines that imaging is appropriately not recommended for the majority of patients with spinal pain. However, despite the proposed benefits of following the guidelines (cost-savings, reductions in exposure to ionizing radiation, avoiding the identification of pathology that may simply represent normal variants, and potentially misinforming clinical decision making), adherence to guidelines is quite variable [3638], and it is largely unknown if adherence results in improved outcomes. Furthermore, there remains a lack of a gold standard quantitative metric for diagnosing low back and neck pain.…”
Section: Imaging Guidelinesmentioning
confidence: 99%